Learning from Vernacular Architecture: Ecological Solutions in Traditional Erzurum Houses - Kirbas, Berrak; Hizli, Neslinur (ELSEVIER SCIENCE BV, 2016)
Vernacular architecture has been an inspiration for innovations in environmental and socio-economically sustainable design and planning. Especially in traditional housing, the intended climatic and environmental solutions within sustainable design have already been achieved by local implementations. In this sense, as the important examples on vernacular architecture, traditional Erzurum houses are examined in the scope of this work. Thus, ecological design clues in local examples are explored by drawing attention to natural materials, traditional construction techniques, ingenious design and spatial organization strategies required for comfort, satisfaction, and well-being of building occupants. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: vernacular architecture; ecological solutions; traditional Erzurum houses; local implementations; Science & Technology - Other Topics; Public Administration; Urban Studies